A gift to remember : a novel - Hill, Melissa, 1974- (St. Martin's Griffin, 2014)
"Darcy Archer works in a small bookstore in Manhattan. A daydream believer, she refuses to settle for anything less than being swept off her feet by the perfect man--literally. One day, when cycling to work, Darcy accidentally crashes into a sharply dressed gentleman walking his dog. He is knocked out cold, rushed to hospital--and the poor pup gets left behind. Wracked with guilt, Darcy takes the dog and makes plans to reunite him with his owner, Aidan"--